ANALYSIS OF THE FACTORS INFLUENCING INDONESIA'S COFFEE EXPORTS IN 2000-2020 - Hasanah, Rifa Uswatun; Prasetyanto, Panji Kusuma (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
Indonesia engages in a variety of export activities, one of which is the export of coffee commodities, with the goal of boosting the country's overall revenue. Coffee is one of Indonesia's primary exports, making it one of the world's leading exporting nations. The purpose of this study is to determine the factors that influence the export of coffee commodities from Indonesia during the period of 2000-2020. An error correction model is utilized in the process of carrying out the analysis approach. The finding revealed that both in the short term and the long term, the price of coffee on the global market has an effect on Indonesia's coffee exports. The exchange rate for the rupiah has no effect on Indonesia's coffee exports in the short term, but it does have an effect on those exports in the long term. There is neither a short-term nor a long-term impact brought about by the quantity of coffee that is produced in Indonesia.